P2 type sodium ion positive electrode material and preparation method thereof

By preparing P2 type sodium ion positive electrode material with single crystal morphology, using co-precipitation method and acid gas treatment, the structural failure and cycle stability of the material at high temperatures are solved, and the cycle life and electrochemical performance of the battery are improved.

CN119133431APending Publication Date: 2024-12-13NANTONG JINTONG ENERGY STORAGE POWER NEW MATERIAL CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411245088.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-09-03
Filing Date
2024-09-06
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

When the charging voltage of P2 sodium ion battery positive electrode material is greater than 4.0V, there is phase change and sodium ion vacancies in an orderly rearrangement, which affects the cyclic stability of the material. The hygroscopicity of the layered structure leads to a decrease in performance, and in severe cases, it leads to a jelly-like condition. , cannot be applied.

Method used

The P2 sodium ion positive electrode material with single crystal morphology is Nax(FeaMn1-aAy)O2. The precursor is prepared by co-precipitation method, and the particle size is controlled to be between 2 and 8 μm. Pure water and acid gas are used during the sintering process. Treatment to ensure uniformity and stability of the material.

Benefits of technology

It improves the mechanical strength and electrochemical properties of the material, reduces the contact surface between the active material and the electrolyte, extends the cycle life of the battery, and suppresses the phase change caused by the Jahn-Teller effect, improving the cycle stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133431A_ABST
    Figure CN119133431A_ABST
Patent Text Reader

Abstract

The chemical formula of the material is Na < x > (Fe Mn < 1-a > A < y >) O < 2 >, x is more than or equal to 0.66 and less than or equal to 0.92, a is more than or equal to 0.3 and less than or equal to 0.6, and y is more than or equal to 0.01 and less than or equal to 0.1. The method comprises the steps that pure water is added into a kettle to serve as an initial base solution, a mixed salt solution of ferric salt and manganese salt is prepared, and the total molar concentration of the solution is 1-2 mol / L; preparing a precipitator; enabling the mixed salt solution and a precipitant to enter a reaction kettle for reaction according to a flow velocity-volume ratio of 1: (0.8-1) in a parallel flow manner, stopping the reaction until the particle size is 2-8 microns, and sequentially performing washing, positive pressure filtration, drying and screening to obtain a carbonic acid series sodium ion positive electrode material precursor; mixing the precursor, a sodium salt and a dopant according to a ratio; the mixture is subjected to staged sintering, and acidic gas is introduced in the cooling stage; and cooling, crushing, carrying out airflow crushing, and screening to obtain the P2-type sodium ion positive electrode material. The material disclosed by the invention is good in electrochemical performance, cycling stability and battery capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion positive electrode materials, and in particular to a P2 type sodium ion positive electrode material and a preparation method thereof. Background Art

[0002] Sodium is the second most abundant element on earth, with abundant reserves, wide distribution and low cost. This gives sodium-ion batteries a significant advantage in raw material costs. In addition to low raw material costs, the production process of sodium-ion batteries is relatively simple, and the manufacturing cost is lower. Sodium-ion batteries are superior to lithium-ion batteries in terms of rate performance, low-temperature performance and safety performance. These performance advantages make sodium-ion batteries competitive in specific application scenarios.

[0003] Layered sodium ion battery cathode materials show strong hygroscopicity when exposed to air. Hygroscopicity can cause physical and chemical changes in the materials, such as water intercalation between TMO2 layers, the formation of protonated phases, and the insertion of carbonate groups, which can reduce the performance of the battery. In severe cases, it can directly cause the cathode slurry to become jelly-like and cannot be slurried and coated. During the charge and discharge process, sodium ions enter and leave the interlayer gaps of layered metal oxides, causing the expansion and contraction of the layered structure. This structural change can easily cause structural damage and capacity decay of layered metal oxides, thereby affecting the cycle life of sodium batteries. Sodium ion cathode materials are divided into four types according to the different ways of Na+ occupation, namely P2, O2, P3 and O3, among which P2 and O3 phases are the most widely studied. In the P2 structure, transition metal ions will not migrate to the sodium layer and sodium ions can migrate between adjacent triangular prisms. The migration barrier is smaller than that of the O3 structure material. However, when the charging voltage is greater than 4.0V, the P2 material has phase change and orderly rearrangement of sodium ion vacancies, which affects the cycle stability of the material.

[0004] Therefore, how to prepare a P2 type sodium ion battery positive electrode material with high air stability, good capacity and high cycle performance is the research content of the present invention. Summary of the invention

[0005] The object of the present invention is to provide a P2 type sodium ion positive electrode material and a preparation method thereof.

[0006] In order to achieve the above-mentioned purpose, the technical solution adopted by the present invention at the material level is:

[0007] A P2 type sodium ion positive electrode material is a layered material with a single crystal morphology, and its chemical formula is: Na x (Fe a Mn 1-a A y )O2, where 0.66≤x≤0.92, 0.3≤a≤0.6, 0.01≤y≤0.1.

[0008] In order to achieve the above-mentioned purpose, the technical solution adopted by the present invention at the process level is:

[0009] A method for preparing a P2 type sodium ion positive electrode material, comprising:

[0010] Step 1: Add pure water into the reactor as the initial base liquid, the amount added is 40-70% of the volume of the reactor;

[0011] A mixed binary metal salt solution of iron salt and manganese salt is prepared, wherein the total molar concentration of the mixed binary metal salt solution is 1 to 2 mol / L;

[0012] Prepare precipitant;

[0013] Step 2, the mixed binary metal salt solution and the precipitant are flowed into the reactor in a flow rate volume ratio of 1:0.8-1 to react with the initial bottom liquid, the reaction temperature is 40-65°C, the pH of the entire reaction system is controlled to be 7-8.5, an inert gas is introduced as a protective gas throughout the process, the reaction is stopped after the particle size is 2-8 μm, and washing, positive pressure filtration, drying, and sieving are performed in sequence to obtain a carbonate-based sodium ion positive electrode material precursor;

[0014] Step 3, mixing the precursor prepared in step 2, the sodium salt and the dopant in proportion to obtain a mixture, wherein the mixing molar ratio of the sodium salt and the precursor satisfies: Na: (Fe + Mn) = 0.66 to 0.92: 1, and the dopant is 1 to 10 wt% of the total amount of the precursor and the sodium salt;

[0015] The mixture is placed in a tube furnace, and sintered in stages under an oxygen atmosphere, with the temperature increasing at a rate of 3 to 5° C. / min, and when the temperature reaches 800 to 1000° C., the temperature is kept for 10 to 20 hours;

[0016] Then, the temperature is lowered at a rate of 2°C / min. During the cooling stage, acid gas is passed through with a flow rate of 50 to 200 L / h.

[0017] Step 4: After cooling, the mixture is crushed, air flow crushed and sieved to obtain a P2 type sodium ion positive electrode material.

[0018] According to a further technical solution, in step 1, the precipitant is one or more of sodium carbonate, sodium bicarbonate, ammonium carbonate, ammonium bicarbonate, and diammonium carbonate, preferably ammonium bicarbonate.

[0019] According to a further technical solution, in step 2, the stirring speed is 300 to 650 rpm / min, preferably 500 to 600 rpm.

[0020] According to a further technical solution, in step 2, the reaction temperature is preferably 50-60°C.

[0021] According to a further technical solution, in step 2, the reaction is stopped after the particle size reaches 2.5 to 3.5 μm.

[0022] According to a further technical solution, in step three, the sodium salt is one or more of sodium hydroxide, sodium carbonate, sodium sulfate, sodium citrate, sodium oxalate, sodium chloride, sodium phosphate, and sodium pyrophosphate, preferably sodium carbonate.

[0023] According to a further technical solution, in step three, the mixing molar ratio of the sodium salt and the precursor satisfies: Na:(Fe+Mn)=0.73-0.82:1.

[0024] According to a further technical solution, in step three, the dopant is one or more of CuO, MoO2, ZnO, TiO2, and MgO, preferably ZnO, and the addition amount is 4%.

[0025] According to a further technical solution, in step three, the flow rate of oxygen is 300-1500 L / h, 500-1000 L / h.

[0026] A further technical solution is that in step three, the staged sintering includes a low-temperature stage and a high-temperature stage. The temperature of the low-temperature stage is 300-500°C, preferably 450-550°C, and the insulation time is 2-6h, preferably 3-5h; the high-temperature stage is 800-1000°C, preferably 850-950°C, and the insulation time is 10-20h, preferably 15-18h.

[0027] According to a further technical solution, in step three, the acidic gas introduced during the cooling stage is one of SO2, CO2, NO2 and HCl, and the introduction time is 1 to 10 hours.

[0028] The terms “include,” “including,” “have,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0029] The terms used herein generally have the ordinary meanings of each term used in the art, in the context of the present invention, and in the specific context, unless otherwise noted. Certain terms used to describe the present invention will be discussed below or elsewhere in this specification to provide additional guidance to those skilled in the art regarding the description of the present invention.

[0030] The working principle and advantages of the present invention are as follows:

[0031] The present invention provides a method for preparing a sodium ion positive electrode material, wherein 40-70% of the volume of a reactor is added as an initial bottom liquid, and then a metal salt solution and a precipitant are mixed at the same time, and after reacting to a target particle size, a precursor is obtained by washing, filtering, and drying, and then the precursor and the sodium salt are sintered in stages, and in the cooling stage, oxygen is switched to an acidic gas, and after cooling, a P2 type sodium ion positive electrode material is obtained by crushing and screening. The primary particles of the precursor of the present invention are in a block shape, and are easily sintered into a positive electrode material with a single crystal morphology.

[0032] The beneficial effects of the present invention are as follows:

[0033] 1. The present invention adopts the co-precipitation method to prepare the precursor, and the obtained precursor material has good morphology uniformity, small particle size and narrow diameter distance.

[0034] Small-size particles can easily melt at high temperatures to form single-crystal particles. Single-crystal particles do not have grain boundaries of secondary particles, have good mechanical strength, are not easy to break during the charge and discharge process, have a stable interface, and have large primary particles and a large specific surface area, which reduces the contact area between the active material and the electrolyte and improves the electrochemical properties of the material.

[0035] 2. The present invention replaces oxygen with a trace amount of acidic gas during the sintering cooling stage, which effectively alleviates the amount of residual alkali generated in the material, improves the coating uniformity, increases the utilization rate of active materials in the battery, and thus increases the battery capacity.

[0036] 3. The addition of a small amount of dopant ZnO in the present invention can inhibit the phase change caused by the Jahn-Teller effect during the charge and discharge process, thereby improving the cycle stability of the battery material. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Attached Figure 1 This is a SEM image of the sodium ion positive electrode precursor material prepared in Example 1 of the present invention;

[0038] Attached Figure 2 The XRD patterns of Example 3 and Comparative Examples 1 and 2 of the present invention are shown below:

[0039] Attached Figure 3 This is a SEM image of the sodium ion positive electrode material prepared in Example 3 of the present invention;

[0040] Attached Figure 4 This is a SEM image of the sodium ion positive electrode material prepared in Comparative Example 1 of the present invention;

[0041] Attached Figure 5 This is a SEM image of the sodium ion positive electrode material prepared in Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0042] The present invention will be further described below in conjunction with the accompanying drawings and embodiments:

[0043] Embodiment: The present invention will be clearly described below with diagrams and detailed descriptions. After understanding the embodiments of the present invention, any person skilled in the art can make changes and modifications based on the techniques taught by the present invention without departing from the spirit and scope of the present invention.

[0044] The terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting of the present disclosure.

[0045] Embodiment 1:

[0046] Add pure water into the reactor as the initial bottom liquid, the amount added is 70% of the volume of the reactor;

[0047] Weigh ferrous sulfate heptahydrate and manganese sulfate to prepare a metal salt solution, the molar ratio of Fe to Mn is 30:70, and the total molar concentration of the metal salt solution is 2 mol / L;

[0048] Prepare 2 mol / L ammonium bicarbonate solution as a precipitant;

[0049] The metal salt solution and the ammonium bicarbonate solution were flowed into the reactor in parallel at a flow rate of 1:0.85 per minute by volume to react with the initial bottom liquid. The pH of the overall reaction system was controlled to be 7-8 by adjusting the flow rate of ammonium bicarbonate, the reaction temperature was 55°C, the reaction time was 28 hours, and the reaction was stopped when the particle size grew to 3.5 μm. The carbonate precursor was obtained by washing, positive pressure filtration and drying.

[0050] Then the above-mentioned precursor and sodium carbonate are weighed according to a molar ratio of 1:0.82, and 4wt% of ZnO based on the total mass of the precursor and the sodium salt is weighed as a dopant. The precursor, sodium carbonate and the dopant are evenly mixed and staged sintering is carried out in an oxygen atmosphere, and the temperature is kept at 450°C for 5 hours, then raised to 900°C for 18 hours. After the insulation, the temperature is cooled at a rate of 2°C / min. SO2 gas is passed during the cooling stage for 5 hours at a flow rate of 100L / h. After cooling to room temperature, it is crushed and sieved to obtain a P2 phase layered sodium ion battery positive electrode material.

[0051] Embodiment 2:

[0052] Add pure water into the reactor as the initial bottom liquid, the amount added is 70% of the volume of the reactor;

[0053] Weigh ferrous sulfate heptahydrate and manganese sulfate to prepare a metal salt solution, the molar ratio of Fe to Mn is 30:70, and the total molar concentration of the metal salt solution is 2 mol / L;

[0054] Prepare 2 mol / L ammonium bicarbonate solution as a precipitant;

[0055] The metal salt solution and the ammonium bicarbonate solution were flowed into the reactor in parallel at a flow rate of 1:0.85 per minute by volume to react with the initial bottom liquid. The pH of the overall reaction system was controlled to be 7-8 by adjusting the flow rate of ammonium bicarbonate, the reaction temperature was 55°C, the reaction time was 28 hours, and the reaction was stopped when the particle size grew to 3.5 μm. The carbonate precursor was obtained by washing, positive pressure filtration and drying.

[0056] Then the above-mentioned precursor and sodium carbonate are weighed in a molar ratio of 1:0.82, and 4wt% of ZnO based on the total mass of the precursor and the sodium salt is weighed as a dopant. The precursor, sodium carbonate and the dopant are evenly mixed and staged sintering is carried out in an oxygen atmosphere. The temperature is kept at 450°C for 5 hours, and then increased to 900°C for 18 hours. After the insulation, the temperature is cooled at a rate of 2°C / min. CO2 gas is passed during the cooling stage for 5 hours at a flow rate of 100L / h. After cooling to room temperature, it is crushed and sieved to obtain a P2 phase layered sodium ion battery positive electrode material.

[0057] Embodiment 3:

[0058] Add pure water into the reactor as the initial bottom liquid, the amount added is 70% of the volume of the reactor;

[0059] Weigh ferrous sulfate heptahydrate and manganese sulfate to prepare a metal salt solution, the molar ratio of Fe to Mn is 30:70, and the total molar concentration of the metal salt solution is 2 mol / L;

[0060] Prepare 2 mol / L ammonium bicarbonate solution as a precipitant;

[0061] The metal salt solution and the ammonium bicarbonate solution were flowed into the reactor in parallel at a flow rate of 1:0.85 per minute by volume to react with the initial bottom liquid. The pH of the overall reaction system was controlled to be 7-8 by adjusting the flow rate of ammonium bicarbonate, the reaction temperature was 55°C, the reaction time was 28 hours, and the reaction was stopped when the particle size grew to 3.5 μm. The carbonate precursor was obtained by washing, positive pressure filtration and drying.

[0062] Then the above-mentioned precursor and sodium carbonate are weighed in a molar ratio of 1:0.82, and 4wt% of ZnO based on the total mass of the precursor and the sodium salt is weighed as a dopant. The precursor, sodium carbonate and the dopant are evenly mixed and staged sintering is carried out in an oxygen atmosphere, and the temperature is kept at 450°C for 5 hours, then increased to 900°C and kept for 18 hours. After the insulation, the temperature is cooled at a rate of 2°C / min. During the cooling stage, NO2 gas is passed for 5 hours at a flow rate of 100L / h. After cooling to room temperature, it is crushed and sieved to obtain a P2 phase layered sodium ion battery positive electrode material.

[0063] Embodiment 4:

[0064] Add pure water into the reactor as the initial bottom liquid, the amount added is 70% of the volume of the reactor;

[0065] Weigh ferrous sulfate heptahydrate and manganese sulfate to prepare a metal salt solution, the molar ratio of Fe to Mn is 30:70, and the total molar concentration of the metal salt solution is 2 mol / L;

[0066] Prepare 2 mol / L ammonium bicarbonate solution as a precipitant;

[0067] The metal salt solution and the ammonium bicarbonate solution were flowed into the reactor in parallel at a flow rate of 1:0.85 per minute by volume to react with the initial bottom liquid. The pH of the overall reaction system was controlled to be 7-8 by adjusting the flow rate of ammonium bicarbonate, the reaction temperature was 55°C, the reaction time was 28 hours, and the reaction was stopped when the particle size grew to 3.5 μm. The carbonate precursor was obtained by washing, positive pressure filtration and drying.

[0068] Then the above-mentioned precursor and sodium carbonate are weighed according to a molar ratio of 1:0.82, and 4wt% of ZnO based on the total mass of the precursor and the sodium salt is weighed as a dopant. The precursor, sodium carbonate and the dopant are evenly mixed and staged sintering is carried out in an oxygen atmosphere, and the temperature is kept at 450°C for 5 hours, then increased to 900°C and kept for 18 hours. After the insulation, the temperature is cooled at a rate of 2°C / min. NO2 gas is passed during the cooling stage for 8 hours at a flow rate of 100L / h. After cooling to room temperature, it is crushed and sieved to obtain a P2 phase layered sodium ion battery positive electrode material.

[0069] Embodiment 5:

[0070] Add pure water into the reactor as the initial bottom liquid, the amount added is 70% of the volume of the reactor;

[0071] Weigh ferrous sulfate heptahydrate and manganese sulfate to prepare a metal salt solution, the molar ratio of Fe to Mn is 30:70, and the total molar concentration of the metal salt solution is 2 mol / L;

[0072] Prepare 2 mol / L ammonium bicarbonate solution as a precipitant;

[0073] The metal salt solution and the ammonium bicarbonate solution were flowed into the reactor in parallel at a flow rate of 1:0.85 per minute by volume to react with the initial bottom liquid. The pH of the overall reaction system was controlled to be 7-8 by adjusting the flow rate of ammonium bicarbonate, the reaction temperature was 55°C, the reaction time was 28 hours, and the reaction was stopped when the particle size grew to 3.5 μm. The carbonate precursor was obtained by washing, positive pressure filtration and drying.

[0074] Then the above-mentioned precursor and sodium carbonate are weighed according to a molar ratio of 1:0.82, and 4wt% of ZnO based on the total mass of the precursor and the sodium salt is weighed as a dopant. The precursor, sodium carbonate and the dopant are evenly mixed and staged sintering is carried out in an oxygen atmosphere, and the temperature is kept at 450°C for 5 hours, then increased to 900°C and kept for 18 hours. After the insulation, the temperature is cooled at a rate of 2°C / min. During the cooling stage, NO2 gas is passed for 3 hours at a flow rate of 100L / h. After cooling to room temperature, it is crushed and sieved to obtain a P2 phase layered sodium ion battery positive electrode material.

[0075] Comparative Example 1:

[0076] The preparation method and sintering process of the precursor and positive electrode material are consistent with those in the embodiment, except that oxygen is still used during the cooling stage, and no other gas is switched.

[0077] Comparative Example 2:

[0078] The preparation method and sintering process of the precursor and positive electrode material are consistent with those in the embodiment, except that there is no dopant.

[0079] Physical and chemical tests:

[0080] The structures of the positive electrode materials of the sodium ion batteries prepared in Example 4 and Comparative Example 1 were characterized using an X-ray diffractometer. Figure 2 As shown, XRD shows that the positive electrode material is a P2 phase layered sodium ion positive electrode with no obvious impurity peaks, indicating that the P2 phase positive electrode material is successfully synthesized using the method of the present invention. Figure 3 ) and Comparative Example 1 ( Figure 4 ) was used for morphological characterization, and it can be seen that the prepared sodium ion positive electrode material has a single crystal morphology, and the primary particles are blocky, thick and large.

[0081] The positive electrode materials, acetylene black and PVDF prepared in Examples 1-5 and Comparative Example 1 were weighed, mixed and stirred in a ratio of 9:0.5:0.5 to prepare slurry, applied, dried for 12 hours, cut into circular electrode pieces, assembled into batteries and tested for performance.

[0082] A certain amount of the positive electrode materials prepared in Examples 1-5 and the comparative example were weighed to measure the pH value of the samples, the content of sodium hydroxide (NaOH) in the residual alkali on the surface, and the viscosity of the slurry mixed with the binder and the conductive agent. The results are as follows:

[0083] Table 1 pH value, surface sodium hydroxide content and viscosity of mixed slurry of positive electrode materials prepared in Examples 1-5 and Comparative Examples 1 and 2

[0084] Sample name pH NaOH content % Mixed slurry viscosity mPa·s Example 1 12.39 0.194 3979 Example 2 12.35 0.166 3638 Example 3 12.10 0.057 3071 Example 4 12.15 0.074 3268 Example 5 12.26 0.138 3584 Comparative Example 1 12.95 0.358 10453 Comparative Example 2 12.64 0.236 6429

[0085] By comparing the embodiments and comparative example 1, the results show that when oxygen is switched to acidic gas during the sintering cooling stage, the pH value of the positive electrode material and the NaOH content in the residual alkali on the surface are significantly reduced compared with the case where oxygen is used throughout the sintering process, and the viscosity of the slurry after the positive electrode material is mixed with the adhesive, the conductive agent, and NMP is also significantly reduced, indicating that the use of trace acidic gas in the sintering cooling stage of the positive electrode material of the present invention is beneficial to the reduction of residual alkali on the material surface and the reduction of slurry viscosity, thereby preventing the layered sodium ion positive electrode material from being slurried into a jelly state.

[0086] Electrochemical performance test:

[0087] Examples 1-5 and Comparative Examples 1 and 2 were pulped in the above-mentioned ratio of 9:0.5:0.5, with the composite sodium sheet as the negative electrode, PP / PE as the separator, and 1M NaClo4 PC+FEC as the electrolyte, and were assembled into 2032 button batteries in order. The battery was tested for electrochemical performance at 0.1C, 2.0-4.05V in a battery test cabinet at room temperature 25°C. By comparing the first-cycle discharge capacity and 100-cycle cycle retention rate of Examples 1-5 and Comparative Examples 1 and 2 at 0.1C, it can be found that the first-cycle discharge capacity of Examples 1-5 is generally higher than that of Comparative Example 2, and the 100-cycle retention rate of Comparative Example 2 is significantly lower than that of Examples 1-5, indicating that doping ZnO effectively inhibits the irreversible phase change of P2-type layered oxides during the cycle process and improves the cycle retention rate of battery materials.

[0088] Table 2 Electrochemical test results of different embodiments and comparative examples

[0089] Sample name 0.1C discharge capacity (mAh / g) <![CDATA[100 th Retention rate (%)]]> Example 1 144.27 85.21 Example 2 145.12 84.48 Example 3 150.52 90.35 Example 4 143.26 86.47 Example 5 143.21 85.38 Comparative Example 1 144.01 89.32 Comparative Example 2 140.49 79.39

[0090] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A P2 type sodium ion positive electrode material, characterized in that: It is a layered material with a single crystal morphology, and its chemical formula is: Na x (Fe a Mn 1-a A y )O2, where 0.66≤x≤0.92, 0.3≤a≤0.6, 0.01≤y≤0.

1.

2. A method for preparing a P2 type sodium ion positive electrode material, characterized in that: For preparing the P2 type sodium ion positive electrode material according to claim 1, the preparation method comprises: Step 1: Add pure water into the reactor as the initial base liquid, the amount added is 40-70% of the volume of the reactor; A mixed binary metal salt solution of iron salt and manganese salt is prepared, wherein the total molar concentration of the mixed binary metal salt solution is 1-2 mol / L; Prepare precipitant; Step 2, the mixed binary metal salt solution and the precipitant are flowed into the reactor in a flow rate volume ratio of 1:0.8~1 to react with the initial bottom liquid, the reaction temperature is 40~65°C, the pH of the entire reaction system is controlled to be 7~8.5, and an inert gas is introduced as a protective gas throughout the process. The reaction is stopped after the particle size is 2~8μm, and washing, positive pressure filtration, drying, and sieving are performed in sequence to obtain a carbonate-based sodium ion positive electrode material precursor; Step 3: Mix the precursor prepared in step 2, the sodium salt and the dopant in proportion to obtain a mixture, wherein the mixing molar ratio of the sodium salt and the precursor satisfies: Na: (Fe + Mn) = 0.66-0.92: 1, and the dopant is 1-10wt% of the total amount of the precursor and the sodium salt; The mixture is placed in a tube furnace, and sintered in stages under an oxygen atmosphere, with the temperature increasing at a rate of 3-5°C / min, and when the temperature reaches 800-1000°C, the temperature is kept at that temperature for 10-20 hours; Then, the temperature was lowered at a rate of 2°C / min. During the cooling stage, acid gas was passed through with a flow rate of 50-200 L / h. Step 4: After cooling, the mixture is crushed, air flow crushed and sieved to obtain a P2 type sodium ion positive electrode material.

3. The method for preparing a P2 type sodium ion positive electrode material according to claim 2, characterized in that: In step 1, the precipitant is one or more of sodium carbonate, sodium bicarbonate, ammonium carbonate, ammonium bicarbonate, and diammonium carbonate.

4. The method for preparing a P2 type sodium ion positive electrode material according to claim 2, characterized in that: In step 2, the stirring speed is 300-650 rpm / min.

5. The method for preparing a P2 type sodium ion positive electrode material according to claim 2, characterized in that: In step three, the sodium salt is one or more of sodium hydroxide, sodium carbonate, sodium sulfate, sodium citrate, sodium oxalate, sodium chloride, sodium phosphate, and sodium pyrophosphate.

6. The method for preparing a P2 type sodium ion positive electrode material according to claim 2, characterized in that: In step three, the dopant is one or more of CuO, MoO2, ZnO, TiO2, and MgO.

7. The method for preparing a P2 type sodium ion positive electrode material according to claim 2, characterized in that: In step three, the flow rate of oxygen is 300~1500 L / h.

8. The method for preparing a P2 type sodium ion positive electrode material according to claim 2, characterized in that: In step three, the staged sintering includes a low-temperature stage and a high-temperature stage. The temperature of the low-temperature stage is 300-500°C, and the insulation time is 2-6 hours; the high-temperature stage is 800-1000°C, and the insulation time is 10-20 hours.

9. The method for preparing a P2 type sodium ion positive electrode material according to claim 2, characterized in that: In step three, the acidic gas introduced during the cooling stage is one of SO2, CO2, NO2, and HCl, and the introduction time is 1 to 10 hours.

Citation Information

Cited By

  • Sodium-ion battery and preparation method of modified positive active material of sodium-ion battery

    CN119864398A